Revisiting the Relevance of Conceptualism of Godard's film Journal for Religion, Film and Media - Vuk Uskokovic (Journal for Religion, Film and Media, 2018)
Jean-Luc Godard's filmmaking is analyzed as a conceptual art, as in agreement with his most accomplished role as a film critic, not a classical filmmaker. In his 1970 manifesto, Godard argues that 1) we must make political films, and 2) we must make films politically. While the first point provokes a constructive critique of the art of cinema, the other one leads to the provision of an absolute cinematic experience. Correspondingly, it is argued that albeit rare and systematically unsupported in the academic setting, a most prolific scientific work is such that it implicitly questions the dominant presentation styles and methodological paradigms in parallel with providing meaningful basic and/or practical findings. The relevance of other elements of Godard's conceptual approach to revolutionizing the art of cinema to scientific studies is elaborated too. The importance of ad hoc improvisation, deliberate imperfectness, the aesthetics of poverty, the embracement of collective uncertainties and the eagerness to constantly get lost to be found is particularly emphasized. "I don't make movies; I make cinema" is Godard's precept whose translation to any professional field, including scientific research and teaching, could produce uncountable benefits. Godard's art is intimately tied to the iteration of the point that the value of an act is measured by the extent to which it reaches out away from the subject and into the world, correlating with the Buberian ontology. Corresponding annihilations of the protagonists symbolize the necessity of the artist's working against the self in the attempt to use her art to destroy the art in question and point at everything as an equally precious art. The discourse follows an impulsive and unstructured course so as to veritably reflect Godard's approach to filmmaking.